Legitimizing private school policy within a political divide: the role of international references - Alessandra Dieudé (Taylor & Francis Group, 2021)
Researchers are increasingly emphasizing the importance of international actors' influence on defining education policy in different contexts. The article argues that referencing international organizations is a way of legitimizing changes to private school policy. Using Norway as an example, the article investigates how international references are used by the political divide: first, a centre-right government liberalized private school policy. This was reversed by the successive centre-left government, before the successive centre-right government again liberalized private school policy. The study draws on content analysis of policy documents from 2002 to 2018. The analysis displays the eclectic nature of how international references are used to (de)legitimize private school policies. Different governments have used similar international references either to legitimise the liberalization of private schooling policy, or to delegitimise such policy. However, the analysis also shows that concepts like free choice, diversity and competition are central in legitimising private school policy. The study of international referencing in the education field  indicates several consequences for the Norwegian education welfare state ideal, such as emphasising a stronger market-orientation. This study shows that analysing how actors position political arguments is important when understanding how nation states, as proactive entities, negotiate meaning and evidence from international references.